ANALISIS FAKTOR YANG MEMENGARUHI NIAT PENGGUNA PADA GOPAY DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Priska Liliani (STIE Wiyatamandala, 2020)
The purpose of this research is determine the factors that influence user intentions on gopay and determine the factors that most influence user intentions on gopay. This research was conducted on 50 respondents in Tangerang and Jakarta who have experience using the gopay application. User intention factors that will be carried out in the research include Applicable, Flexible, Controllable, Effectiveness, Usefulness, Benefits, Compatibility, Recommendation, Reuse Intention, and Pay More. With the factor analysis test, a group of factors is formed which is the TAM factor. Using ranking values from factor analysis can identify the factors that most influence the use of gopay.